2003
DOI: 10.1021/jm020375q
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal Activity of Conformationally Restricted Pentamidine Congeners

Abstract: A series of conformationally restricted congeners of pentamidine in which the flexible pentyl bridge of pentamidine was replaced by trans-1,2-bismethylenecyclopropyl, phenyl, pyridinyl, piperazinyl, homopiperazinyl, and piperidinyl groups were synthesized. The compounds were evaluated for trypanocidal activity in vitro and in vivo against one drug-sensitive and three drug-resistant trypanosome isolates. The DNA binding affinity of the compounds was also studied using calf thymus DNA and poly(dA-dT). The nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 27 publications
2
78
0
1
Order By: Relevance
“…[48][49][50] In a recent article, Donkor et al studied the trypanocidal activity of a series of conformationally restricted congeners of pentamidine. 15 Although a direct correlation between the DNA binding affinity and the trypanocidal activity was not observed, the authors concluded that compounds with strong DNA affinity generally showed good trypanocidal activity in that series. In particular, N,N'-bis(4-amidinophenyl)piperazine (Figure 1) and N,N'-bis(4-imidazolinophenyl)piperazine were the most potent trypanocides and also the strongest DNA binders in this series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50] In a recent article, Donkor et al studied the trypanocidal activity of a series of conformationally restricted congeners of pentamidine. 15 Although a direct correlation between the DNA binding affinity and the trypanocidal activity was not observed, the authors concluded that compounds with strong DNA affinity generally showed good trypanocidal activity in that series. In particular, N,N'-bis(4-amidinophenyl)piperazine (Figure 1) and N,N'-bis(4-imidazolinophenyl)piperazine were the most potent trypanocides and also the strongest DNA binders in this series.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Moreover, some of the alkanediguanidine [1, 8-octanediguanidine (1b), 29 1,12-dodecanediguanidine (1d), 6,30,31 bis(guanidinopropyl)amine (6a) 32 trypanosomal agent in vivo. 15 Hence, in the search for new HAT chemotherapy, we decided to carry out an in vitro screening against the parasite T. brucei rhodesiense of a total of 62 compounds (Tables 1-5) taken from our in-house library and structurally related to the trypanocidal agents synthalin (1,10-decanediguanidine) and 4,4'-diguanidinodiphenylmethane (31b), and the polyamine N 1 -(3-amino-propyl)-propane-1,3-diamine respectively. We also describe here the original synthesis of 21 molecules which had not been previously reported.…”
Section: Toc Graphicmentioning
confidence: 99%
“…1A). We have been interested (12,24,25,31,34) in determining the effect of restricting the conformational flexibility of pentamidine congeners on their anti-P. carinii and antiparasitic activity. Based on these recent studies, we identified 4,4Ј-(1,4-piperazinediyl)bisbenzenecarboximidamide (compound 19, Table 1) as a promising lead compound.…”
mentioning
confidence: 99%
“…Amidinophenyl substituted benzo and pyridine dicarboxamides were prepared and tested for their antimicrobial activity or cytotoxic activity against several human cancer cell lines [12][13][14][15]. Although they showed moderate activity against P. carinii and Plasmodium falciparum, their poor antitumor activity was poor [6,14,16].…”
Section: Introductionmentioning
confidence: 99%